2001
DOI: 10.1093/jat/25.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Non-Prescription Heroin Markers in Urine with Liquid Chromatography--Atmospheric Pressure Chemical Ionization Mass Spectrometry

Abstract: The planned introduction of a prescription heroin program in Germany created a need for differentiation between non-prescription and prescribed diamorphine use. The following substances were chosen as markers of non-prescription heroin: acetylcodeine (AC); its metabolites codeine (C) and codeine 6-glucuronide (C6G); papaverine (P); and noscapine (N). Typical heroin markers diamorphine (DAM) and its metabolites monoacetylmorphine (MAM) and morphine (M) were also determined. The drugs were extracted from urine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…Any of the nonpsychoactive opium alkaloids shown in Table 1 [4][5][6][7][8][9][10][11] is a potential marker of opium use if it is detected in urine together with morphine and codeine. However, because some of these alkaloids have sources other than opium (Table 1), the unequivocal confi rmation of opium use requires the detection of as many alkaloids as possible for a test sample.…”
Section: Introductionmentioning
confidence: 99%
“…Any of the nonpsychoactive opium alkaloids shown in Table 1 [4][5][6][7][8][9][10][11] is a potential marker of opium use if it is detected in urine together with morphine and codeine. However, because some of these alkaloids have sources other than opium (Table 1), the unequivocal confi rmation of opium use requires the detection of as many alkaloids as possible for a test sample.…”
Section: Introductionmentioning
confidence: 99%
“…The LC-MS/MS procedure used in the present study permitted the simultaneous determination of nine substances which are considered as general markers of heroin use or rather as specific markers of illicit heroin abuse [2,[4][5][6]. The procedure is useful for the analytical differentiation between prescribed pharmaceutical heroin use and illicit heroin abuse on the basis of urine analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Codeine (COD) was most frequently detected as an additional marker substance in urine of illicit heroin users, but only its acetylated form, acetylcodeine (AC), was considered as a definite biomarker [2]. Otherwise, AC was found in fewer specimens and in lower concentrations than 6AM [3,4], and due to a short half-life of approximately 237 min [5], it was not detectable in urine for as long as morphine following heroin abuse [5,6]. Therefore, it was concluded that the detection of urinary metabolites of the opiate alkaloids noscapine (NOS) and papaverine (PAP) is useful for an analytical differentiation between the use of illicit heroin and pharmaceutical diacetylmorphine, which is free from further substances [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is a frequent carryover impurity in illicit heroin powder; its contents are about 10% (w/w) in the Pakistani type 1 and Iranian heroin, and only trace in Chinese, Indian, Pakistani type 2, and Turkish heroin [2]. It was also reported as a major adulterant of illicit heroin [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Noscapine [2] and its metabolites, meconin and desmethylmeconin [10], have been detected in urine and proposed as markers of illicit heroin use, in differentiation from medicinal heroin (diamorphine) use. We published some reports highlighting the use of the marker compounds, such as reticuline and neopine, for proving the illicit use of opium and opiate products [11,12].…”
Section: Introductionmentioning
confidence: 99%